Sink-source relations in cassava: Effects of reciprocal grafting on yield and leaf photosynthesis - Pellet, D; El-Sharkawy, Mabrouk A. (Cambridge University Press, 1994)
Two contrasting clones of cassava (Manihot esculenta) were reciprocally grafted to test the hypothesis that the yield of cassava is limited by the number of storage roots. Effects of the root sink on leaf gas exchange were also tested under field conditions using a portable infra-red gas analyzer. Storage root number and root yield were affected by stock size and root yield was associated with the number of storage roots. The harvest index and sink-source ratio (root numberz/leaf area index) were correlated with root number. A feedback effect of root number on single-leaf photosynthesis was observed in one clone. It is concluded that the number of storage roots may be used as an indicator of sink strength.